(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Economies that are afflicted by a high level of corruption—which involves the misuse of power in the form of money or authority to achieve certain goals in illegal, dishonest, or unfair ways—are not capable of prospering as fully as those with a low level of corruption.